Emotional dysregulation in patients with anorexia nervosa - Sak Леся; Khaustova Олена (Psychosomatic Medicine and General Practice, 2019)
Intoduction. Eating disorders, including anorexia nervosa, are common, severe, and often chronic mental disorders. The debate over the pathogenesis and supporting factors of anorexia nervosa continue because therapeutic interventions do not lead to satisfactory and long-lasting remission rates and persistent (resistant) forms of the disease are increasingly common. Several of English-language studies with a fundamental analysis that indicates a direct influence of psychoemotional state and/or existing psychopathological manifestations in parents on the development of eating disorders, including anorexia nervosa. Historically negative family dynamics are indicated as a key element in the development of anorexia nervosa, along with personality vulnerabilities. Emotional dysfunction within the family and interaction with individual personality traits contribute to the development and maintenance of anorexia nervosa. Concerning individual personality traits, studies have shown that anorexia nervosa in female adolescents is associated with difficulties in emotional regulation, which are associated with obsessive-compulsive / perfectionist and impulsive personality traits. However, the analysis of the array of Ukrainian-language scientific literature accumulated in recent years on this issue has not yet been made. Understanding the cause and effect of anorexia nervosa and treatment-resistant forms of the disease is a necessary prerequisite for further research and development of new effective approaches to therapy. Goal. Determining the current state of analysis of the problem of emotional regulation in patients with anorexia nervosa in Ukraine in comparison with world scientific developments. Describe a clinical case showing a violation of emotional regulation in a patient with anorexia nervosa. Materials. Qualitative and quantitative content analysis and concept analysis were conducted using meta-analyses and systematic reviews of scientific Ukrainian-language and English-language literature published for the period from January 2015 to December 2019. Results. Dysfunctional emotional processing and regulation play an important role in the development and maintenance of anorexia nervosa. Systematic reviews indicate that people with anorexia nervosa have difficulty with emotional awareness (including alexithymia and poor emotional clarity), along with high levels of disgust and shame. The limitations of modern theories of anorexia nervosa and the context of the phenomenological and interpersonal nature of the disorder led to the emergence of the theory of the organizing function of the mind "I" in anorexia nervosa. According to this theory, anorexia nervosa occurs against the background of vague emotional experience as a means of regulating emotions and restoring the sense of bodily "I", which is determined by the judgments and appearance of others. Studies also show that patients with anorexia nervosa have particularly low rates of reflex function. Low reflexive functioning together with low consistency of opinion is a consequence of uncertainty in attachment and is manifested by increased anxiety of attachment or avoidance of attachment. The clinical significance of attachment dynamics for patients with anorexia nervosa is underscored by the association between greater attachment anxiety and the avoidance and symptoms of eating disorders. The above clinical case demonstrates a violation of emotional regulation in a patient with anorexia nervosa. The combination of psychotherapeutic methods (individual and family psychotherapy), which were aimed at correcting the "I" and adaptive changes in reflexive functioning, together with medical intervention, allowed to obtain positive results of treatment, as evidenced by the annual follow-up. Conclusions. At the heart of anorexia nervosa is marked dysfunctional emotional processing and regulation. Patients with anorexia nervosa have low rates of reflex function. The practical significance of the model of anorexia nervosa as a disorder, which is supported by difficulties with emotional experience, is proved by the application of their provisions in the psychotherapeutic process in real clinical practice. Developing interventions to improve emotional regulation skills in the treatment of patients with anorexia nervosa, in combination with family psychotherapy, can be an important component in improving treatment outcomes, reducing relapses, and developing resistant forms of the disease.